2021
DOI: 10.1007/s10741-021-10129-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical variants of myocardial involvement in COVID-19-positive patients: a cumulative experience of 2020

Abstract: Myocardial injury, diagnosed by troponin elevation, is common in COVID-19 patients, but cardiac involvement with clinical manifestations occurs less frequently. We analyzed the literature on COVID-19 (2020) and systematically reviewed the cases where individual patient data were presented. We searched PubMed and Google Scholar for "COVID," "COVID-19," and "coronavirus" in combination with "myocarditis," "heart failure," "takotsubo," "cardiomyopathy," and "cardiogenic shock." We identified 90 cases of COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 92 publications
0
10
1
1
Order By: Relevance
“…One of the most common is myocarditis that may be characterized by myocardial damage in the absence of ischemic causes and inflammatory infiltrates [ 65 , 66 ]. In almost a third of COVID-19 patients with myocardial involvement, cardiogenic shock occurred [ 67 ] with a mortality of about 26% [ 68 ]. In addition, COVID-19 patients have a high risk of arterial and venous thrombosis [ 69 ].…”
Section: Extrapulmonary Manifestations and The Role Of Gut Microbiota...mentioning
confidence: 99%
“…One of the most common is myocarditis that may be characterized by myocardial damage in the absence of ischemic causes and inflammatory infiltrates [ 65 , 66 ]. In almost a third of COVID-19 patients with myocardial involvement, cardiogenic shock occurred [ 67 ] with a mortality of about 26% [ 68 ]. In addition, COVID-19 patients have a high risk of arterial and venous thrombosis [ 69 ].…”
Section: Extrapulmonary Manifestations and The Role Of Gut Microbiota...mentioning
confidence: 99%
“…Myocardial injury seen during SARS-CoV-2 infection may be due to myocardial infarction caused by plaque rupture (type 1 myocardial infarction), increased myocardial demand (type 2 myocardial infarction), or stress cardiomyopathy or myocarditis, all of which leads to increased troponin levels, commonly seen in COVID-19 25 , 26 , 27 . Differential diagnosis between myocardial infarction, myocarditis or stress cardiomyopathy will require conventional complementary tests, among which electrocardiography, echocardiography and cardiac magnetic resonance (CMR) or angiography will be of great importance.…”
Section: Cardiac Manifestations During Sars-cov-2 Infectionmentioning
confidence: 99%
“…In critically ill patients, troponin is often positive because of acute respiratory distress, inflammation, and coagulation disorders (2), even in absence of significative coronary stenosis (3). Previous studies reported the occurrence of a myocardial involvement, defined as increased troponin levels and electrocardiographic abnormalities, among hospitalized COVID-19 patients (4).…”
Section: Introductionmentioning
confidence: 99%